(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the relationship between thought, language, and faith as a philosophical problem based on historical sources. From ancient philosophers to medieval religious and philosophical teachings, as well as views in modern and contemporary philosophy, are considered in a comparative approach. In the study, thinking is interpreted as the main activity of human consciousness, and language as the social and cultural expression of this thinking. Faith, on the other hand, is based on the fact that it regulates the relationship between thinking and language through spiritual and moral criteria. Through the analysis of historical sources, the role of this triad in the spiritual life of society, the formation of worldview, and the development of social consciousness is highlighted. The results of the article serve to expand the possibilities of applying the trinity of thinking-language-belief in modern socio-philosophical research.